Norbornenyl-pendant aromatic (co)poly(ether ether ketone)s - Talanikar, Aniket A.; Nagane, Samadhan S.; Wadgaonkar, Prakash P.; Rashinkar, Gajanan S. (Journal of macromolecular science part A- pure and applied chemistry, 2023)
4, 4'-(Bicyclo (2.2.1) hept-5-en-2 yl methylene) bis (2-methoxyphenol) (BPA-NB) was utilized as a step-growth monomer for the synthesis of (co)poly(ether ether ketone)s (PEEK-NBs) via nucleophilic aromatic substitution polycondensation. A homo and five PEEK-NBs were synthesized by polycondensation of 4, 4'-difluorobenzophenone with BPA-NB and various compositions of BPA-NB and bisphenol-A, respectively. H-1 NMR spectroscopy confirmed the chemical structure and composition of PEEK-NBs. Inherent viscosity and number-average molecular weight values of PEEK-NBs were in the range 0.64 to 0.78 dL g(-1) and 62,670 to 84,470 g mol(-1), respectively, indicating the formation of polymers of reasonably high molecular weight. It was easy to dissolve PEEK-NBs in common organic solvents such as chloroform, dichloromethane, and tetrahydrofuran. Tough, transparent, and flexible films of PEEK-NBs could be cast from chloroform solution. X-Ray diffraction studies indicated amorphous nature of PEEK-NBs. Glass transition temperature (T-g) values, determined by DSC analysis, of PEEK-NBs were in the range 163 to190 degrees C and T-g values increased with the increase in mol % of BPA-NB. The post-polymerization modification of a representative PEEK-NB was demonstrated using two azido compounds, namely, 4-(azidomethyl)-7-methoxy-2H-chromen-2-one and 9-(azidomethyl)anthracene, via metal-free azide-alkene 1,3-dipolar cycloaddition reaction to obtain copoly(ether ether ketone)s appended with coumarinyl and anthracenyl moieties, respectively.
Keywords: (Co)poly(ether ether ketone)s; azide-alkene click reaction; norbornenyl groups; post-polymerization modification